Illuminating the Supreme Leader's Viewpoint toward the Concept of Health System: A Content Analysis-Based Qualitative Study - Mansour Kheirgoo; Habib Dehghan (Shahid Beheshti University of Medical Sciences, 2017)
For downloading the full-text of this article please click here. Background and Objective: In today's society, health is among the top priorities of every state. The importance of this concept can be observed in the economic, cultural and social potential of healthy human resources in each community. This article examines the components and indicators of health and also presents a conceptual model for it based on the supreme leader's viewpoint. Method: Content analysis was utilized in this qualitative study to illuminate the concepts, indicators and components of health and wellness based the supreme leader's ideas. The sample included all health-related statements mentioned by Ayatollah Khamenei in his speeches delivered between March, 2001 and March, 2017. These data were retrieved from library categorizations. In this study, the ethical issues were all observed. Additionally, the authors declared no conflict of interests. Results: In total, 18 key health indicators were identified in the supreme leader's speeches: national production, progress in work, scientific initiative, development and advancement, preservation of scientific discourse, speed of scientific progress, fulfillment of assigned tasks, risk taking, prioritizing, talent, cultural issues, proper treatment of patients, future-oriented vision, correct attitude, commercialization, education, sports and general health. Conclusion: According to the findings of the study, from the supreme leaders' perspective, thre three main elements of health-related subjects are dynamism, self-sufficiency and globalization. Inspired by these statements, we can build a healthier society, which is economically stronger and has a higher level of public satisfaction. Following the supreme leader's health-related guidelines can eventually lead to having a more powerful and self-sufficient country. For downloading the full-text of this article please click here.